SUSTAINABILITY-ORIENTED ENTREPRENEURSHIP: STRATEGI MEMBANGUN EKONOMI HIJAU BERBASIS KOMUNITAS LOKAL - Wahib, Moh; Stafrezar, Burhan; Sadiqin, Amin (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Sustainability-oriented entrepreneurship (SOE) has emerged as a crucial catalyst in the transition toward a green economy, particularly at the local community level where participation and indigenous knowledge can be mobilized to generate contextual and inclusive solutions (Patzelt & Shepherd, 2011). This qualitative study aims to analyze the key strategies employed by sustainability-oriented entrepreneurs in developing community-based green economy models in Indonesia. A multi-case study design was applied to 6 entrepreneurial initiatives in the sectors of agro-ecotourism, renewable energy, and waste management. Data were collected through in-depth interviews, participant observation, and document analysis.The findings identify three core strategies: (1) strengthening social capital and collaborative governance to enable risk-sharing and access to collective resources; (2) local resource-based value innovation, transforming raw materials and traditional knowledge into high value-added products and services while minimizing ecological footprints; and (3) consumer education and empowerment, fostering environmentally conscious markets and reinforcing social legitimacy (York & Venkataraman, 2010). Key challenges include limited access to green financing, fragmented policy support, and overreliance on charismatic leadership.The novelty of this study lies in integrating sustainability-oriented entrepreneurial strategy analysis with a community-based green economy perspective in the context of a developing country, an area that remains underexplored in existing literature.The study concludes that community-based SOE has strong potential to become the backbone of a resilient green economy. It recommends the development of an integrated support ecosystem—including dedicated green financing schemes, green business incubation, and policy incentives for multi-stakeholder collaboration—to enhance replication and scalability.